Radiologic progression of glioblastoma under therapy—an exploratory analysis of AVAglio. Issue 4 (1st September 2017) - Nowosielski, Martha; Ellingson, Benjamin M; Chinot, Olivier L; Garcia, Josep; Revil, Cedric; Radbruch, Alexander; Nishikawa, Ryo; Mason, Warren P; Henriksson, Roger; Saran, Frank; Kickingereder, Philipp; Platten, Michael; et al.
Abstract: Background: In this exploratory analysis of AVAglio, a randomized phase III clinical study that investigated the addition of bevacizumab (Bev) to radiotherapy/temozolomide in newly diagnosed glioblastoma, we aim to radiologically characterize glioblastoma on therapy until progression and investigate whether the type of radiologic progression differs between treatment arms and is related to survival and molecular data. Methods: Five progression types (PTs) were categorized using an adapted algorithm according to MRI contrast enhancement behavior in T1- and T2-weighted images in 621 patients (Bev, n = 299; placebo, n = 322). Frequencies of PTs (designated as classic T1, cT1 relapse, T2 diffuse, T2 circumscribed, and primary nonresponder), time to progression (PFS), and overall survival (OS) were assessed within each treatment arm and compared with molecular subtypes and O 6 -methylguanine DNA methyltransferase ( MGMT ) promoter methylation status. Results: PT frequencies differed between the Bev and placebo arms, except for "T2 diffuse" (12.4% and 7.1%, respectively). PTs showed differences in PFS and OS; with "T2 diffuse" being associated with longest survival. Complete disappearance of contrast enhancement during treatment ("cT1 relapse") showed longer survival than only partial contrast enhancement decrease ("classic T1"). "T2 diffuse" was more commonly MGMT hypermethylated. Only weak correlations to molecular subtypes from primary tissue were detected. Conclusions: Progression of glioblastoma under therapy can be characterized radiologically. These radiologic phenotypes are influenced by treatment and develop differently over time with differential outcomes. Complete resolution of contrast enhancement during treatment is a favorable factor for outcome.